Lesotho - Managing Government Finances for Growth and Poverty Reduction : Public Expenditure Management and Financial Accountability Review - World Bank (Washington, DC, 2012)
This report on managing government finances for growth and poverty reduction in Lesotho is centered on three areas of analysis: (i) macroeconomic and fiscal performance and prospects; (ii) inter and intra-sectoral allocation of resources; and (iii) public expenditure and financial management. A Public Financial Management assessment report, prepared using the Public Expenditure and Financial Accountability (PEFA) framework is included as an Appendix to the main report. The study stress that despite the relatively good growth performance, Lesotho remains one of the poorest countries in the Southern Africa region. Because of this the Government now seeks to address in a more systematic manner the many challenges facing Lesotho including: 1) the slow pace of job creation in Lesotho, compounded by the continual decline in mining jobs for migrant workers in South Africa and a slowdown in GDP growth rate; 2) the increase in the incidence of poverty over the past twenty years; 3) a relatively large and inefficient public sector; 4) excessive reliance on revenues generated by the Southern Africa Customs Union ; and 5) the rapid spread of HIV/AIDS (current prevalence rate estimated at 24 percent), which, if unchecked, will negate all efforts to improve the economy and welfare of the Basotho people.